An Industrial systems design study on Barrio Fiesta Manufacturing Corporation - Apolinario, Napoleon Jr; Cabardo, Laser; Santeco, Ryan Phillip; Silva, Ronald (College of Engineering, 2001)
Barrio Fiesta Manufacturing Corporation is a company established in 1987 that produces ready to eat meals in cans such as Dinuguan, Binagoongang Baboy, Bopis, and Pork Adobo. This study aims to document, evaluate, improve and/or solve problems in the supply chain management system of the canning division of Barrio Fiesta Manufacturing Corporation, particularly in the areas of: purchasing, inventory management, stores/warehousing, manufacturing, finished goods warehousing operations, transport operations, and customer service operations. The company+s current systems and procedures are documented and analyzed for existing and potential problems in the supply chain. Alternatives are generated for the problems identified and the best alternative is selected based on cost and benefit analysis. Implementation strategies and time schedules for the selected alternatives are then formulated and recommended to Barrio Fiesta Manufacturing Corporation. The root problems identified were the absence of formal purchasing objectives and policies and underutilized space in the finished goods warehousing area. To address the problem of no formal purchasing objectives and policies, the study proponents recommended a complete definition and establishment of a purchasing function against the alternative of doing nothing. Based on the cost-benefit analysis of the alternatives, the recommendation of a purchasing function incurred more costs but its benefits such as having formal contacts with suppliers prompt deliveries, easier procurement of materials, better incoming inspection, and adequate supplier performance evaluation, would outweigh them eventually as compared to the alternative of doing nothing. In dealing with the problem of underutilized space in the finished goods warehousing area, the use of shelves to increase the utilization of storage area was recommended against the alternative of doing nothing. From the cost benefit analysis, the use of shelves will lead to additional production equal to one day full utilization of the finished goods warehouse. For the recommendation of a purchasing function, purchasing objectives, purchasing policies supplier performance evaluation methods, appraisal and control of the purchasing system, and performance measures were recommended. A new facility layout together with the use of shelves was proposed in order to improve production flow and utilization of the storage area. Afterwards, implementation strategies, procedures, schedule and responsibility centers were recommended for both problems addressed. Recommendations and implementations in the project are meant as suggestions for the company. The company may or may not use the information, recommendations, and/or implementations indicated in the project. The study proponents also found areas for further study in the company's system. A demand forecasting system could be studied and utilized so as to simplify production scheduling and give more time for purchasing to acquire needed materials. This would in turn give the purchasing function more time to evaluate supplier proposals, get better deals and ensure continuous production.